Using individual two-posterior short implants with two-anterior standard implants in mandibular implant-supported-overdenture to enhance the patient satisfaction: A clinical report - Mehran Bahrami; Mohammed Hussein M Alsharbaty (Wolters Kluwer Medknow Publications, 2017)
Introduction: Many clinical cases and the literature review have revealed implant-supported-overdentures' (ISOs) treatment success and predictability in elderly patients. According to the previous studies, all the mandibular ISOs used 2-4 implants anterior to mental foramen to retain the denture. Case Report: In this clinical report, two individual anterior standard implants and two individual posterior short implants were used to support the mandibular ISO, as well as to prevent further posterior bone resorption. This treatment option permits the patient to insert more implants in the future, and could be upgraded to implant-supported-fixed prosthesis. Discussion: The patient was completely satisfied about the final result, especially for upgrading the mastication efficiency. The patient was followed-up for more than 2 years without complication. The panoramic X-ray showed the preserved bone in the posterior region. This technique could be considered to be innovative, and more clinical cases are required to be documented as a predictable modality.